الجوانب الوطنية عند المفسرين الإندونسيين باللغة الجاوية - Ali Fahrudin; Syofyan Hadi (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
ملخصقد شاعت الآراء بين الناس قلة الروح القومية لبعض مسلمي إندونيسيا لعدم تقبلهم فكرة ترشح فئات غير مسلمة للزعامة عبر الانتخابات العامة. مع أن هناك عوامل بيئية ودينية تدفع المسلمين لاختيار القادة ولا يتعلق الأمر بالروح الوطنية والتسامح تجاه الأديان الأخرى. تهدف هذه المقالة إلى إثبات أن العلماء الإندونيسين يملكون شعورا قويا نحو الوطن وذلك منذ فترة ما قبل الاستقلال. وهذا ما نجد في بعض مؤلفاتهم لا سيما في كتب التفسير المكتوبة باللغة الجاوية. أما المنهج المستخدم في هذا البحث فهو منهج التفسير الموضوعي حيث يحاول الكاتب توضيح آراء المفسرين المحلييين المكتوبة باللغة الجاوية حول الآيات التي تتناول موضوع "القومية". ونتيجة هذا البحث هي أن العلماء الجاويين لديهم مواقف سامية تجاه الروح القومية. ويتجلى ذلك بوضوح في جوانب عدة منها حب الوطن والتسامح والدفاع عن البلاد. The nationalistic attitude of some Muslims in Indonesia is questioned because they are considered intolerant of non-Muslims, especially non-Muslims who are nominated to be leaders in a Muslim-majority region.  In fact, the tendency to elect a leader is usually motivated by environmental and religious factors, not because of the absence of nationalism and tolerance towards believers of other religions. This article’s purpose is to prove that this nationalism attitude was also owned by Indonesian Islamic scholars in old times, especially local Tafseer (Tafseer is a commentary book of knowledge) scholars in Javanese. This Javanese Tafseer was chosen because it contains native Indonesians wisdom. The method used in this research is a thematic Tafseer method by elaborating on the opinions of Javanese Tafseer scholars on verses related to nationalism. The conclusion of this article reveals that the Javanese Tafseer scholars have very high nationalistic attitudes towards their country. This is reflected in his work which is very prominent in the aspects of love for their homeland, tolerance, and defending the country.